Sti declines among sex workers and clients following outreach, one time presumptive treatment, and regular screening of sex workers in the Philippines. Issue 5 (29th September 2006) - Wi, T; Ramos, E R; Steen, R; Esguerra, T A; Roces, M C R; Lim-Quizon, M C; Neilsen, G; Dallabetta, G
Abstract : Objectives: This intervention linked research aimed to reduce prevalence of Neisseria gonorrhoeae (Ng) and Chlamydia trachomatis (Ct) among female sex workers by means of one round of presumptive treatment (PT), and improved prevention and screening services. Methods: A single round of PT (azithromycin 1 g) was given to all female sex workers reached during a 1 month period of enhanced outreach activity. Routine sexually transmitted infection (STI) screening services were successfully introduced for two groups of unregistered sex workers who work in brothels (BSWs) and on the street (SSWs). No changes were made to existing screening methods for registered sex workers (RSWs) or lower risk guest relations officers (GROs). Cross sectional prevalence of Ng and Ct was measured by PCR on three occasions, and stratified by type of sex work. Ng/Ct prevalence was assessed twice in clients of BSWs. Results: Prevalence of Ng and/or Ct at baseline, 1 month post-PT, and 7 months post-PT was BSWs: 52%, 27%, 23%; SSWs: 41%, 25%, 28%; RSWs: 36%, 26%, 34%; GROs: 20%, 6%, 24%, respectively. Ng/Ct declines 1 month post-PT were significant for all groups. 6 months later prevalence remained low for BSWs (p<0.001), and SSWs (p = 0.05), but had returned to pre-intervention levels for the other groups. Prevalence of Ng/Ct among clients of BSWs declined from 28% early in the intervention to 15% (p = 0.03) 6 months later. Conclusions: In this commercial sex setting, one round of PT had a short term impact on Ng/Ct prevalence. Longer term maintenance of STI control requires ongoing access to effective preventive and curative services.